Necropolitics in OHAL: The state of emergency experience of Turkey (1987-2002) - Has, Özlem. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2017., 2017)
Achille Mbembe has opened a new path for studies of violence with the con-cept “necropolitics” which refers to the “subjugation of life to the power of death.” The Mbembe’s main goal is to reveal the relationships among power, politics, and death, particularly in places where a state of exception is in oper-ation. He claims that disciplinary and biopolitical powers are insufficient to explain the mechanisms of control and subjugation in exceptional spaces; ne-cropolitics is needed if one wants to understand the true workings of power. This thesis discusses the necropolitical violence at the intersection of ne-cropolitics and the state of exception that was in operation during the years of the State of Emergency (Olağanüstü Hal or OHAL), which was put in practice in Southeastern Turkey between 1987 and 2002. This thesis argues how the politics of death was implemented in the OHAL region in light of specific cases from the OHAL period.
Keywords: War and emergency powers -- Turkey.; Human rights -- Turkey.; Martial law -- Turkey.; Kurds -- Turkey.